Internet adoption and usage patterns in Africa: Evidence from Cameroon. (August 2015) - Penard, Thierry; Poussing, Nicolas; Mukoko, Blaise; Tamokwe Piaptie, Georges Bertrand
Abstract: The objective of this paper is to understand what factors stimulate or hinder the adoption and usage of the Internet in Africa. We adopt a micro-econometric approach and use household survey data from Cameroon. Our results show that young and educated individuals are more likely to use the Internet in Cameroon. The probability of using the Internet is also higher for male, as well as for English-speaking and computer savvy individuals. Moreover, Internet users are more likely to have family abroad. We also find that Internet usage patterns differ across gender, age and education. For instance, older generations are less likely to use the Internet as a leisure activity (video, game, music). College educated people are also more likely to go online to search information than to have entertainment usage. These results provide evidence of digital divide in the Internet access, but also in the usage patterns on the African continent in particular in African countries that are at the early stages of Internet diffusion. Highlights: Using household survey data from Cameroon, we study factors explaining Internet adoption and usage patterns in Africa. The adoption decision is mainly driven by the expected utility of being connected and the monetary and cognitive costs. Internet usage patterns are mainly influenced by gender, age, education and computer skills.